A derivation of the generalized model of strains during bending of metal tubes at bending machines - Śloderbach, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
According to the postulate concerning a local change of the ?actual active radius? with a bending angle in the bend zone, a generalized model of strain during metal tube bending was derived. The tubes should be subjected to bending at tube bending machines by the method of wrapping at the rotating template and with the use of a lubricated steel mandrel. The model is represented by three components of strain in the analytic form, including displacement of the neutral axis.
Keywords: bending; metal tubes; bending machine; strains; neutral axis